Anna Murià: biografia, autobiografia, ficcions - Espinós, Joaquim (Caplletra. Revista Internacional de Filologia, 2014)
Anna Murià’s work is on the margins of Catalan exile literature. This article, conceived within the theoretical framework of autobiographical literature, is an attempt to contribute to the clearing up of some of the keys to its interpretation. The fictional and testimonial work of the author makes up a coherent and original autobiographical space.